2018
DOI: 10.2134/jeq2017.07.0292
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Cropping Effects on Partitioning of Water Flow and Nitrate Loss between Surface Runoff and Tile Drainage

Abstract: Surface runoff and tile drainage are the main pathways for water movement and entry of agricultural nitrate into water resources. The objective of this 5-yr study was to characterize the partitioning of water flow and nitrate loss between these pathways for a humid-temperate Brookston clay loam soil under 54 to 59 yr of consistent cropping and fertilization. Cropping treatments included monoculture corn ( L., MC), continuous bluegrass ( L.) sod (CS), and a corn-oat-alfalfa ( L.)-alfalfa rotation (RC-RO-RA1-RA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…At each site, TDN concentrations more than doubled when comparing extreme high-low to extreme low-low observations. his result is not surprising given that the predominant land use in these watersheds is row crop agriculture and the soils are tile drained, which is known to be a primary pathway for N loss (Woodley et al, 2018). he impact of hydrology on TDP was inconsistent across sites.…”
Section: Resultsmentioning
confidence: 99%
“…At each site, TDN concentrations more than doubled when comparing extreme high-low to extreme low-low observations. his result is not surprising given that the predominant land use in these watersheds is row crop agriculture and the soils are tile drained, which is known to be a primary pathway for N loss (Woodley et al, 2018). he impact of hydrology on TDP was inconsistent across sites.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding these factors is critical for choosing the correct management practice(s) to reduce NO 3 –N loss. In temperate climates, most of the drainage (81% in Indiana [Kladivko et al, 2004] and 57 to 97% in Ontario, Canada [Woodley et al, 2018]) occurs during the nongrowing season (November through April). In the northern Corn Belt, where soils are frozen during winter, 60 to 80% of drainage usually occurs in the spring months of April through June, when precipitation often exceeds evapotranspiration (Jaynes et al, 2001; Randall et al, 2003b; Randall and Vetsch, 2005b; Helmers et al, 2012).…”
mentioning
confidence: 99%
“…The studies found through our literature search encompassed sites across the U.S. and Canada and mainly involved implementing different crop rotation systems, applying fertilizer at varying rates, and measuring the chemical contents and amount of subsurface drainage discharge and/or surface runoff for each crop in the rotation or for whole rotations (tables A3 through A7 in the Appendix). Some studies also incorporated other management practices in their evaluations by varying tillage practices and fertilizer type by treatment (e.g., Shipitalo et al, 2013;Weed and Kanwar, 1996;El-Hout and Blackmer, 1990;Woodley et al, 2018). Measurements of drainage or runoff amount and contents were then used by the researchers to evaluate the effectiveness of certain cropping systems in reducing nitrate losses from agricultural fields.…”
Section: Water Quality Benefits From Various Crop Rotation Systemsmentioning
confidence: 99%
“…All of the factors that may influence the amount of N contributed by different legumes to subsequent crops can also impact the magnitude of nitrate losses in legume-corn crop rotation systems. In particular, precipitation (Klocke et al, 1999;Lawlor et al, 2008;Owens et al, 2000), soil characteristics (Wolkowski et al, 1998), and the other agricultural management practices in place, such as irrigation (Klocke et al, 1999), tillage (Daryanto et al, 2017;Drinkwater et al, 2000;Kanwar et al, 1997;Rekha et al, 2011;Shipitalo et al, 2013;Weed and Kanwar, 1996), and different nutrient management strategies (Drinkwater et al, 1998;El-Hout and Blackmer, 1990;Fox et al, 2001;King et al, 2016;Lawlor et al, 2008;Owens et al, 2000;Rekha et al, 2011;Zhu and Fox, 2003;Woodley et al, 2018), can have a significant impact on the amount of N available for loss via leaching or runoff.…”
Section: Water Quality Benefits From Various Crop Rotation Systemsmentioning
confidence: 99%